THE EFFECT OF TECHNOLOGICAL LITERACY, LEARNING FACILITY, AND FAMILY ENVIRONMENT ON STUDENTS’ LEARNING MOTIVATION - Maria Yoroi Andini Fedin; Norlida Hanim Mohd Salleh; Agung Winarno (Graduate School of Universitas Negeri Malang, 2022)
Student achievement is influenced by a variety of factors, both internal and external, such as school and home amenities. This study intends to assess the effect of technological literacy, amenities and learning environment on the learning motivation of SMK students during the pandemic. This is a quantitative Expos-Fact style of study. This study's population and sample consisted of 58 students majoring in Automation and Office Governance at SMK PGRI Turen; questionnaires and observations were used to collect data. Multiple linear regression test was employed for data analysis. The analysis reveals that technical literacy has a favorable influence on learning motivation, that facilities have a positive effect on learning motivation, and that the learning environment has no effect on learning motivation. The environmental impact is not attributable to the fact that a lack of suitable facilities at home is not a motivating factor for student learning.